Determinants of Detectable Anti-hepatitis B in Fertile Age Women from Indonesia - Noer Endah Pracoyo; Made Ayu Lely Suratri; Felly Philipus Senewe; Vivi Setiawaty (Universitas Islam Bandung, 2022)
Hepatitis B (HBV) is still a major health problem worldwide, as evidenced by the large number of people infected with hepatitis. There are around two billion people infected with HBV, and an estimated 350 million are in chronic conditions. Hepatitis B is a ninth-order disease that causes death in mothers and their babies. The HBV infection in pregnant women is critical because of vertical or perinatal transmission. This study's purpose was to analyze data of the HBsAg and anti-HBs rertile age women, pregnant women, and postpartum mothers from National Basic Health Research Data 2007. The method is a retrospective study using secondary data from the Basic Health Research in 2007. The number of samples in the form of data on respondents of fertile age women are women aged 15 to 49 years. Data screened and matched with that examined pregnancy/have had a postpartum examination/never checked neonates/had examined their toddlers. One thousand three hundred two (1,302) respondents were eligible to be sampled in this analysis. The variables analyzed were age and anti-HB titers in women of childbearing age 15 to 49 years who were not protected against hepatitis B, as much as 74.65% of the total 1,302 people. Three hundred thirty (330) respondents had anti-HBs titers. This study concludes respondents who are not married age 15–20 years showed relationship with negative anti-Hbs antibodies.